Analysis of Consumer Preferences for Traditional Pudak Snacks in Gresik Regency (Case Study of Sari Kelapa Gresik Store) - Ningrum, Yulia Retno Fitria; Yektiningsih, Endang; Indah, Pawana Nur (Agridevina : Berkala Ilmiah Agribisnis, 2024)
Pudak is a typical food from the city of Gresik which is made from rice flour or sago flour, granulated sugar and coconut milk in packaging made from a material called "ope", namely the base of the stem of the betel leaf. This research aims to analyze the attributes of traditional Pudak snacks that are consumer preferences and analyze the attributes that consumers most consider at the Gresik coconut sari shop. The analysis used is descriptive analysis and multi-attribute fishbein analysis. The results of the research show that the attributes of traditional pudak snacks that are the preference of consumers at the Gresik coconut sari shop are pudak which has an affordable price, sweet taste, white (original) flavor variant, and longer shelf life (4-5 days). Then, the attribute of traditional pudak snacks that is most considered in consumer purchasing decisions is the taste of pudak. The order of the attributes of the traditional pudak snacks at the Sari Kelapa Gresik shop that are most considered to those that are least considered are pudak taste, flavor variants, shelf life, and price of pudak.